2008
DOI: 10.1007/s11255-008-9359-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of sleep quality between hemodialysis and peritoneal dialysis patients

Abstract: Hemodialysis and peritoneal dialysis patients had a similar high rate of poor sleep quality. Further studies are necessary to investigate the causes of poor quality of sleep and to investigate methods to improve sleep quality in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
38
1
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 15 publications
12
38
1
7
Order By: Relevance
“…Previous studies have concluded that 42-88% of HD patients had sleep problems or disorders such as insomnia [20,22]. In our study, the prevalence of insomnia symptoms according to the AIS scores in nightmare sufferers and the control group was 82% and 25%, respectively.…”
Section: Discussionsupporting
confidence: 43%
“…Previous studies have concluded that 42-88% of HD patients had sleep problems or disorders such as insomnia [20,22]. In our study, the prevalence of insomnia symptoms according to the AIS scores in nightmare sufferers and the control group was 82% and 25%, respectively.…”
Section: Discussionsupporting
confidence: 43%
“…These findings need to be assessed further in view of contradictory results that have been reported earlier [9]. In the same fashion, although diabetes mellitus was found as a predictor for the poor quality of sleep in univariate analysis but in the multivariate model it did not show any significant effect.…”
Section: Discussionmentioning
confidence: 70%
“…Some studies have reported that increasing duration of dialysis, physical health, co-morbidities, burden of kidney disease, sexual function, dyspnea, pain, itching, mean corpuscular volume, serum albumin, and diabetes mellitus worsen the quality of sleep [2,3,9,10]. However, contradictory studies are also available that suggest that quality of sleep in MHD patients is not related to age, gender, biochemical parameters, and other factors mentioned above [4,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are still other factors that can promote changes in behavior, generally related to physical symptoms associated with uremia, like anorexia, fatigue and sleep disorders, common in patients with chronic kidney disease (6)(7) .…”
Section: Introductionmentioning
confidence: 99%